2016
DOI: 10.1021/acs.bioconjchem.6b00585
|View full text |Cite|
|
Sign up to set email alerts
|

Fluorinated and Charged Hydrogenated Alkanethiolates Grafted on Gold: Expanding the Diversity of Mixed-Monolayer Nanoparticles for Biological Applications

Abstract: Low intrinsic toxicity, high solubility, and stability are important and necessary features of gold nanoparticles to be used in the biomedical field. In this context, charged nanoparticles proved to be very versatile, and among them charged mixed-monolayer gold nanoparticles, displaying monolayers with well-defined morphologies, represent a paradigm. By using mixtures of hydrogenated and fluorinated thiols, the formation of monolayer domains may be brought to an extreme because of the immiscibility of fluorina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Along this line, Pasquato and coworkers combined approaches for preparing MPNPs by using mixtures of amphiphilic fluorinated and amphiphilic hydrogenated thiols bearing polyethylene glycol units of very different lengths (Bidoggia et al. 2017 ; Gentilini et al. 2009 ; Pengo and Pasquato 2015 ; Posocco et al.…”
Section: How Spontaneous Ligand Organization Generates Nanoscale Compmentioning
confidence: 99%
“…Along this line, Pasquato and coworkers combined approaches for preparing MPNPs by using mixtures of amphiphilic fluorinated and amphiphilic hydrogenated thiols bearing polyethylene glycol units of very different lengths (Bidoggia et al. 2017 ; Gentilini et al. 2009 ; Pengo and Pasquato 2015 ; Posocco et al.…”
Section: How Spontaneous Ligand Organization Generates Nanoscale Compmentioning
confidence: 99%
“…However, cofunctionalization of NPs with mixtures of polar and apolar ligands is not an easy task: earlier studies showed that such processes typically result in preferential adsorption of only one of the two ligands. Among numerous other examples, Bishop and co-workers found that performing ligand exchange on DDA-capped 6 nm Au NPs with an 8:1 mixture of octadecanethiol and ω-mercaptoundecanoic acid resulted in a 0.35:1 mixture of these two ligands on the functionalized NPs, whereas Meli et al reported that a 3:1 molar ratio of dodecanethiol and ω-mercaptoundecanol used to functionalize 4 nm NPs was increased up to 32:1 as a result of the ligand exchange reaction . The discrepancy between the solution and the on-NP ratio typically originates from attractive/repulsive interactions between the ligands or when one of the ligands induces NP precipitation during the functionalization process.…”
Section: Introductionmentioning
confidence: 99%
“…The monolayer stabilizes the core and can be tailored with a range of functionalities to provide effective cellular uptake, controlled payload release, and cell-specific targeting [50]. Direct covalent attachment to the gold core can be used to deliver thiolated fluorophores [51] or small molecule drugs into the cell and into tumor tissue [52] with improved efficacy over free drug [53]. These coverings are stable outside cells but labile intracellularly due to much higher glutathione levels inside cells than extracellularly, providing a mechanism for internal release [54].…”
Section: Gold Particlesmentioning
confidence: 99%